CX3CR1 Deficiency Alters Hippocampal-Dependent Plasticity Phenomena Blunting the Effects of Enriched Environment - Maggi, Laura; Scianni, Maria; Branchi, Igor; D'Andrea, Ivana; Lauro, Clotilde; Limatola, Cristina (Frontiers in Cellular Neuroscience, 2011)
In recent years several evidence demonstrated that some features of hippocampal biology, like neurogenesis, synaptic transmission, learning and memory performances are deeply modulated by social, motor and sensorial experiences. Fractalkine/CX3CL1 is a transmembrane chemokine abundantly expressed in the brain by neurons, where it modulates glutamatergic transmission and long-term plasticity processes regulating the intercellular communication between glia and neurons, being its specific receptor CX3CR1 expressed by microglia. In this paper we investigated the role of CX3CL1/CX3CR1 signaling on experience-dependent hippocampal plasticity processes. At this aim wt and CX3CR1GFP/GFP mice were exposed to long-lasting-enriched environment (EE) and the effects on hippocampal functions were studied by electrophysiological recordings of long-term potentiation (LTP) of synaptic activity, behavioral tests of learning and memory in the Morris water maze paradigm and analysis of neurogenesis in the subgranular zone of the dentate gyrus (DG). We found that CX3CR1 deficiency increases hippocampal plasticity and spatial memory blunting the potentiating effects of EE. In contrast, exposure to EE increased the number and migration of neural progenitors in the DG of both wt and CX3CR1GFP/GFP mice. These data indicate that CX3CL1/CX3CR1-mediated signaling is crucial for a normal experience-dependent modulation of hippocampal functions.